Purification and Characterization of Linamarse from Gadung (Dioscorea hispida Dennst) for Gadung Slurry Detoxification - Harijono, Harijono; N., Siwi; Sutrisno, Aji (Jurnal Teknologi Pertanian, 2011)
The aim of this research was to find out purification of enzyme linamarase fromDioscorea hispida Dennts. Enzyme purification was carried out by amonium sulphatefractionation and Sephadex G-75 gel filtration coloumn chromatography. Protein purifyfactor achieved was 10.5 times, protein yield was 33.3 % of the crude cell extract proteinand specific activity was 2.93 U/mg. The enzyme purity of each purification stage wasmonitored by SDS-PAGE and resulted one protein band. The optimum temperature andpH of enzyme reaction was 57°C and pH 6.5 with 90 minutes incubation. Using crudelinamarin as substrat, linamarase has Km 0.1564 μmol ml and Vmax 0.2796μmol/minute. Pure linamarase was added in Dioscorea slurry to increase cyaniderelease. Keywords: purification, characterization, linamarase, detoxification, Dioscorea hispidaDennts.